Advokasi terhadap Pelacuran Anak di Lokalisasi Dolly Surabaya - Hartono, Hartono (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2013)
This article discusses about advocacy against child prostitution in Dolly-Surabaya. Child prostitution is an act that violates the fundamental rights of the children from any kind of exploitation activities. The people who cause prostitution are to be punished in accordance with the applied regulations. Advocacy on child prostitution in Dolly is where the act of prostitution is not getting any penalties or sanctions because the child only has an obligatory capability and not an act capability. The parties that led to the child victims of prostitution should be punished by the assumption that they have done fraud and coercion. Moreover, child prostitution is a form of human trafficking. The advocacy dedicated to child as the victim of prostitution is: first, litigation advocacy with the target of those children’s fundamental rights which have been violated by others can be restored; second, budgetary advocacy with the goal of keeping the budget managed by the government can be allocated appropriately to children who become the victim of prostitution; and third, policy advocacy with the aim of protecting the fundamental rights and improving the welfare of the children who become the victim of prostitution, both of morally and materially.